กลวิธีทางภาษาในการประกอบสร้างพื้นที่ศักดิ์สิทธิ์ ในนวนิยายสัจนิยมมหัศจรรย์ เรื่อง “นางพญาอสรพิษ” - คุณารักษ์, กิตติยา; เพ็งประภา, พรพิมล (วารสารศรีล้านช้างปริทรรศน์, 2021)
บทความวิชาการนี้มีวัตถุประสงค์เพื่อศึกษากลวิธีทางภาษาในการประกอบสร้างพื้นที่ศักดิ์สิทธิ์ในนวนิยายสัจนิยมมหัศจรรย์เรื่องนางพญาอสรพิษของ ตรี อภิรุม โดยใช้กรอบแนวคิดด้านพื้นที่ศักดิ์สิทธิ์ แนวคิดสัจนิยมมหัศจรรย์ และแนวคิดการประกอบสร้างความหมาย เลือกศึกษาใน 6 ประเด็น ได้แก่ 1) ภาษาเล่าความจริง 2) ภาษาสร้างความเหนือจริง 3) ภาษาสร้างอารมณ์ 4) ภาษาสื่อความก้าวร้าวรุนแรง 5) ภาษาสื่อความคิดทางการเมือง 6) ภาษาจากคำยืมบาลีสันสกฤต ผลการศึกษาพบว่า พื้นที่ศักดิ์สิทธิ์ในนวนิยายสัจนิยมมหัศจรรย์เรื่องนางพญาอสรพิษของ ตรี อภิรุม มีการประกอบสร้างผ่านภาษา ดังนี้ 1) ภาษาเล่าความจริง เป็นการเสนอเนื้อหาเรื่องราวที่ใช้ภาษาแทรกเรื่องเล่าอิงประวัติศาสตร์ของยุคสมัย 2) ภาษาสร้างความเหนือจริง เป็นการสร้างความเหนือจริงเกี่ยวกับความลี้ลับของผู้คน รวมถึงเรื่องวิญญาณ โดยตั้งคำถามกับความตายและเรื่องเหนือธรรมชาติ 3) ภาษาสร้างอารมณ์ เป็นการสร้างอารมณ์ความรู้สึกให้ผู้อ่านเกิดอารมณ์คล้อยตามในความเชื่อของกฎแห่งกรรม 4) ภาษาสื่อความก้าวร้าวรุนแรง เป็นเรื่องเลียนแบบเหตุการณ์จริงในสังคมแล้วแทรกจินตนาการของชีวิตมนุษย์อย่างตรงไปตรงมา 5) ภาษาสื่อความคิดทางการเมือง เป็นการนำเสนอในรูปการถกเถียงเกี่ยวกับปรัชญาการเมืองและเสนอในรูปการต่อสู้ทางการเมือง 6) ภาษาจากคำยืม เป็นการใช้ภาษาสันสกฤตและภาษาบาลีที่เป็นศัพท์สูงที่ใช้สื่อความหมายด้านหลักธรรมทางพุทธศาสนา คำสำคัญ: กลวิธีทางภาษา; การประกอบสร้างความหมาย; พื้นที่ศักดิ์สิทธิ์; นวนิยายสัจนิยมมหัศจรรย์; นางพญาอสรพิษ; Abstract                The objective of the academic article was to study the linguistic strategies in the construction of the sacred space in Tri Aphirum’s magical realism novel Nang Phya Asoraphit (Queen Snake),” based upon the concepts of sacred space, magical realism, and meaning construction. Tri Aphirum was a pseudonym or a pen name of Thep Chumsai Na Ayutthaya, honoured and praised as one of Thailand’s national artists in the field of literary art. The sacred space was studied through six linguistic strategies, namely, 1) realistic narration, 2) surrealistic narration, 3) emotional narration, 4) narration on offense and violence, 5) narration on political thoughts, and 6) borrowings from Pali and Sanskrit. The study revealed that the sacred space in Tri Aphirum’s magical realistic novel Nang Phya Asoraphit was constructed through the following linguistic strategies: 1. The realism was periodically inserted and described through the historical narratives at that time. 2. The surrealism was proclaimed through people’s beliefs in enigmatic mysteries, including a soul, with some questions on death and supernatural things. 3. The emotional narration was aimed at encouraging the readers to go along with the fiction and believe in the law of action (Karma). The offense and violence were differently narrated by imitating the social events in reality and exactly expanding them through the writer’s imagination in human life. 5. The narration of political thoughts at that time was communicated in the formations of political philosophical discussion and political struggle. 6. Pali and Sanskrit words, regarded as the high-class alternatives, were borrowed to communicate Buddhist teachings. Keywords : Linguistic Strategy; Meaning Construction; Sacred Space; Magical Realistic Novel; Nang Phya Asoraphit;